Motivasi Kerja Sebagai Faktor Penentu Kinerja Guru: Literatur Review - Wiyana As’ari; Muhammad; Edi Muhamad Jayadi (Mataram University, 2026)
This study aims to analyze the role of work motivation as a determining factor in improving teacher performance through a literature review approach. The method used is a literature review by examining 10 scientific articles published between 2020-2025 related to work motivation and teacher performance. Data were collected through documentation study and analyzed using descriptive analysis with a synthesis approach to compare and interpret previous research findings. The results indicate that work motivation has a positive effect on teacher performance, however, the level of significance varies depending on contextual and supporting factors. Teachers with high work motivation tend to demonstrate better performance in planning, implementing, and evaluating learning processes. However, several studies reveal that the contribution of work motivation to teacher performance is relatively small compared to other factors such as work discipline, leadership, and work environment. Therefore, work motivation is an important factor in improving teacher performance, but it cannot stand alone. A comprehensive approach considering various influencing factors is needed to achieve optimal teacher performance